2022
DOI: 10.3390/life12020221
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Kerosene on Microbiomes of Diverse Soils

Abstract: One of the most important challenges for soil science is to determine the limits for the sustainable functioning of contaminated ecosystems. The response of soil microbiomes to kerosene pollution is still poorly understood. Here, we model the impact of kerosene leakage on the composition of the topsoil microbiome in pot and field experiments with different loads of added kerosene (loads up to 100 g/kg; retention time up to 360 days). At four time points we measured kerosene concentration and sequenced variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“… Hu et al (2022) found that Chloroflexi was negatively correlated with TN content, consistent with our results of lower Chloroflexi abundance in the NPK and NPKGM treatments. As typical copiotrophic taxa, both Acidobacteria and Planctomycetota usually dominate in barren conditions ( Fierer et al, 2007 ; Shelyakin et al, 2022 ) and thus were enriched in our CK treatment.…”
Section: Discussionmentioning
confidence: 99%
“… Hu et al (2022) found that Chloroflexi was negatively correlated with TN content, consistent with our results of lower Chloroflexi abundance in the NPK and NPKGM treatments. As typical copiotrophic taxa, both Acidobacteria and Planctomycetota usually dominate in barren conditions ( Fierer et al, 2007 ; Shelyakin et al, 2022 ) and thus were enriched in our CK treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Two soil samples (20 kg, natural moisture) of the A-horizons of Dystric Arenosols and Albic Luvisols were sieved using sieves with a mesh of 3 mm, cleaned of roots and other coarse fraction, dried to the air-dry state in the lab. Then, they were moistened by distilled water added in small portions to a level of 60% of the maximum field capacity using a dispenser [4] . Addition of water was estimated by gravimetrically.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…In 288 soil samples, kerosene concentration was determined using the method thoroughly described in [4 , 9] and briefly in Table 6 . In 96 soil samples (one mixed sample of the triplicate replicas, Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method gives reproducible and reliable results on the biochemical activity of soil microorganisms in a wide range of soils, e.g. Retisols, Arenosols, Chernozems, Histosols, Regosols, Technosols [ 5 , 25 ], including those under hydrocarbon pollution [ 6 , 26 , 27 ].…”
Section: Final Remarksmentioning
confidence: 99%